Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1111/j.1365-2621.2004.tb09941.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electron Beam Irradiation on the Bacterial Load and Sensorial Quality of Sliced Cantaloupe

Abstract: Electron beam irradiated sliced cantaloupe was tested for 21 d of storage for total aerobic microbial counts, texture, color, and different sensorial parameters as a function of irradiation doses 0, 0.7, and 1.4 kGy and the wash treatments, 1 and 200 ppm chlorine applied to the melons before cutting. Irradiation resulted in a reduction in the total aerobic microbial counts with increasing doses. Melons washed only with water before cutting had total aerobic bacterial counts of 4.0, 2.0, and 0.8 log colony-form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 23 publications
2
24
0
1
Order By: Relevance
“…This study indicates that EB treatment caused significant reduction of microbial population in dates to below the maximum reference; dependent on the EB dose used. A similar observation has been reported by Palekar et al (2004) on the effect of EB treatment on TVC of cantaloupe, the TVC for the non-treated sample was 4.0 log CFU/g reduced to by 2.0 log CFU/g at 0.7 kGy and 3.8 log CFU/g at 1.4 kGy.…”
Section: Microbial Loadsupporting
confidence: 83%
“…This study indicates that EB treatment caused significant reduction of microbial population in dates to below the maximum reference; dependent on the EB dose used. A similar observation has been reported by Palekar et al (2004) on the effect of EB treatment on TVC of cantaloupe, the TVC for the non-treated sample was 4.0 log CFU/g reduced to by 2.0 log CFU/g at 0.7 kGy and 3.8 log CFU/g at 1.4 kGy.…”
Section: Microbial Loadsupporting
confidence: 83%
“…Quality studies for irradiated fresh-cut cantaloupes indicated that irradiation at 1.4 kGy did not have any effect on the quality or sensory characteristics of the cut melons (Palekar et al, 2004a). Fan et al (2006) reported the effect of gamma irradiation on fresh-cut cantaloupes obtained from fresh cantaloupes that were treated by hot water pasteurization.…”
Section: Irradiationmentioning
confidence: 99%
“…Quality studies for irradiated fresh-cut cantaloupes indicated that irradiation at 1.4 kGy did not have any effect on the quality or sensory characteristics of the cut melons (Palekar et al, 2004a). reported the effect of gamma irradiation on fresh-cut cantaloupes obtained from fresh cantaloupes that were treated by hot water pasteurization.…”
Section: Irradiationmentioning
confidence: 99%